The Role of Side‐Arms for Supramolecular Affinity Materials Based on 9, 9′‐Spirobifluorenes. Issue 24 (28th June 2017) - Pyka, Isabella; Nikl, Joachim; Schollmeyer, Dieter; Waldvogel, Siegfried R.
Abstract : An eightfold functionalized D 2d ‐symmetric 9, 9′‐spirobifluorene was condensed with a collection of diketones with elaborated structural features to form three‐dimensional supramolecular architectures with active surfaces. Gas‐sorption measurements performed with quartz crystal microbalances indicateded remarkable molecular interactions for the application as affinity materials in the detection of volatile organic compounds. Packing motifs obtained by single‐crystal X‐ray structure analysis gave further insights into potential host–guest interactions. Abstract : Appropriately bulky end groups condensed at the 9, 9′‐spirobifluorene backbone essentially influence the three‐dimensional architecture. The potent host–guest interactions were studied with a quartz crystal microbalance. By taking X‐ray structure analysis of suitable crystals into account, tremendous effects onto the binding‐site definition suggest their suitability as affinity materials.